Library User Metaphors and Services : How Librarians Look at Their Users - Hedemark, Åse (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2016)
Carl Gustav Johannsen: Library User Metaphors and Services. How Librarians Look at Their Users. Walter de Gruyter GmbH & Co KG, 2015, 182 s. Lektor Carl Gustav Johannsen har i boken Library User Metaphors and Services. How Librarians Look at Their Users (2015) beskrivit och problematiserat vilka begrepp som biblioteksprofessionella använder när de uttalar sig om sina användare.